DETERMINING THE AMOUNT OF FEED USING INTERNET OF THINGS (IOT) BASED ON TEMPERATURE, pH, AND AMMONIA MONITORING - , M Lutfi Hauzan Tama; Muhamad Dedra Purnama; Rafly Adi Fahrezy; Muhammad Rizki Rifa’i; Ridho Juliansyah; M Isya Rais Ansori; M Ikhsan Hisyam; Risma Rosyada Julian; Almi Dwi Utam; Herlina Indryani; Deby Shinta; Khamila Aulia Salsabi; Wiyoto Wiyoto; Ridwan Iskandar; Ester Angeline; Fiqri Nurfadillah; Muhammad Danang Mukti Darmawan; Nanda Octavia (Jurnal Sains Indonesia, 2024)
The availability of sufficient feed is very important for the success of fish farming. However, fish feeding by farmers is currently still conventional, often irregular and excessive due to human error. To increase production efficiency and yield, automatic feeding technology is needed. One solution is an Automatic Fish Feeder based on the Internet of Things (IoT) which integrates hardware, sensors and software as control. This research aims to provide the optimal amount of feed based on temperature using fuzzy logic. In this study, Fuzzy Logic was designed with the help of Matlab software, which will then be used as a basis for determining the output value of the automatic fish feeding system after implementing Fuzzy Logic. There is a Fuzzy Logic design in Matlab with the Mamdani method which has 1 input variable and 1 output variable. The input variable is the temperature parameter and the output variable is the quantity of fish feed. By applying Fuzzy Logic in determining the quantity of fish feed on automatic feeders, it is hoped that it can help fish farmers who use automatic fish feeders in determining the right amount of feed.